UiTM and Northern Illinois University strengthen ties in sustainability and biodiversity - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
On 29 May 2025, UiTM Global host a visit by Professor Dr. Melissa Lenczewski from Northern Illinois University (NIU). Dr. Lenczewski is a renowned hydrogeologist and Fulbright Scholar known for her impactful work in environmental chemistry, groundwater quality, and sustainability education. The visit was part of UiTM's ongoing efforts to strengthen global academic networks and foster meaningful collaborations in environmental science and sustainability.